Penguatan Karakter Kristiani melalui Kegiatan Sanggar Tari “Kariak Antang” di Sekolah Menengah Atas Kristen Tumbang Samba - Yuel, Yuel; Krisdayanti, Krisdayanti (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the strengthening of Christian character values in extra-curricular activities at the “Kariak Antang” studio at SMAK Tumbang Samba.” This research used a qualitative method. The results revealed that the strengthening of Christian character in extra-curricular activities at the “Kariak Antang” studio at Tumbang Samba Christian Senior High School in the form of dances and songs (karungut) illustrated that the activities of this studio have shown things that are in line with Christian character values and the main development goals contained in the regional motto of Katingan Regency, namely Living in Togetherness (Penyang hinje simpei).